Mullā Ṣadrā’s Epistemological Critique of Modern Skepticism: A Reconstruction of the Foundations of Certainty in Knowledge - Tantriatus Sholehah; Loekisno Choiril Warsito; Ghifroh Nailul Maulidah (Aqlania, 2026)
This paper deals with the epistemic crisis of certainty in modern epistemology, which is provoked by the empirical scepticism of David Hume. Hume doubted the principles of causality and inductive reasoning so much that knowledge is only conceived as probabilistic and contingent mental representations and lacks a firm ontological basis. This results in strong object-subject and empirical reductionism. This study uses qualitative method based on literature study, by applying critical philosophical approach and conceptual analysis to the main texts of the two thinkers. The main finding is that Mullā Ṣadrā in the context of al-Ḥikmah al-Muta‘āliyah, reconstructs the basis of certainty of knowledge through the doctrines of aṣālat al-wujūd (the superiority of existence), tashkīk al-wujūd (the degree of existence), al-‘Ilm al-Ḥuḍūrī (knowledge of presence), Ittiḥād al-‘Āqil wa-al-Ma‘qūl (the oneness of the subject and object of knowledge) and al-ḥarakah al-jawhariyyah (substantial movement). Ṣadrā’s epistemology harmonizes reason (burhān), intellectual intuition (kashf), and revelation (naql), so that knowledge is no longer merely a mental representation, but rather an existential event that unites subject and object at a higher level of existence. This reconstruction has successfully addressed Hume’s skepticism and has initiated a fruitful dialogue between Islamic epistemology and contemporary modern epistemology.